Люмінесцентні властивості халькогенідних стекол, легованих рідкоземельними елементами - Кевшин, Андрій; Kevshyn, Andriy (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті досліджено особливості люмінесцентних властивостей халькогенідних склоподібних напівпро- відників (ХСН), легованих іонами рідкоземельних елементів (РЗЕ). Вважається, що фотолюмінесценція в таких матеріалах може збуджуватися шляхом прямого перерозподілу заселеності внутрішніх 4f рівнів або збуджен- ням матриці скла світлом з енергією порядку оптичної ширини енергетичної щілини ХСН та її передачею РЗЕ.; In this paper the luminescent properties of chalcogenide glasses doped with rare earth elements were investigated. In particular, we consider the scheme of the process of energy transfer in chalcogenide glasses doped with rare-earth elements, as well as up-conversion and cross-relaxation transitions in a pair of Er3+ ions. It is shown that in the glasses (X) (Er2Se3) – (100-X) (20 mol.% Ga2Se3 – 80 mol.% GeSe2) with high content of erbium, which is approaching the limit of solubility (Х>0.5 mol.% Er2Se3) clusters of Er atoms occur, that due to the cooperative up-conversion or crossrelaxation damping lead to reduction of the intra-centre luminescence.
Luminescent Properties of Chalcogenide Glasses Doped With Rare Earth Elements
Keywords: склоподібні сплави; фотолюмінесценція; рідкоземельні елементи; glassy alloys; photoluminescence; rare earth elements